The magic rabbit - Cate, Annette (Cambridge, Mass. : Candlewick Press, 2007)
When Bunny becomes separated from Ray, a magician who is his business partner and friend, he follows a crowd to a park where he has a lovely afternoon, and after the people leave and darkness falls, the lonely and frightened Bunny finds a glittering trail of hope.
Keywords: Rabbits -- Juvenile fiction; Lost articles -- Juvenile fiction; Magicians -- Juvenile fiction; Lost and found possessions -- Fiction